X‐ray spectrometry and imaging for ancient administrative handwritten documents†. (13th January 2015) - Albertin, Fauzia; Astolfo, Alberto; Stampanoni, Marco; Peccenini, Eva; Hwu, Yeukuang; Kaplan, Frédé́ric; Margaritondo, Giorgio
<x xml:space="preserve">Abstract</x> 'Venice Time Machine' is an international program whose objective is transforming the 'Archivio di Stato' – 80 km of archival records documenting every aspect of 1000 years of Venetian history – into an open‐access digital information bank. Our study is part of this project: We are exploring new, faster, and safer ways to digitalize manuscripts, without opening them, using X‐ray tomography. A fundamental issue is the chemistry of the inks used for administrative documents: Contrary to pieces of high artistic or historical value, for such items, the composition is scarcely documented. We used X‐ray fluorescence to investigate the inks of four Italian ordinary handwritten documents from the 15th to the 17th century. The results were correlated to X‐ray images acquired with different techniques. In most cases, iron detected in the 'iron gall' inks produces image absorption contrast suitable for tomography reconstruction, allowing computer extraction of handwriting information from sets of projections. When absorption is too low, differential phase contrast imaging can reveal the characters from the substrate morphology. Copyright © 2015 John Wiley & Sons, Ltd.